Developing Senior High School Students’ Leadership Character through a Gamified Leadership Training Program at SMA Negeri 3 Kota Batam - Siska Amelia Maldin; Rezki Alhamdi; Natal Olotua Sipayung; Dailami; Wahyudi Ilham; Syafruddin Rais; Tito Pratama; Moh. Thanzir; Abd Rahman Yusuf (JURNAL KEKER WISATA, 2026)
This community service program aimed to develop students’ leadership character through a Gamified Leadership Training program implemented at SMA Negeri 3 Kota Batam. The program employed a gamification-based experiential learning approach involving interactive activities such as Leadership Identity Card, Mission Possible, Leader Swap Role Play, Trust Tower Challenge, Leaderboard and Reward System, and Guided Reflection Sessions. The activities were designed to strengthen students’ leadership competencies, including communication, teamwork, critical thinking, responsibility, decision-making, and problem-solving skills. The findings indicate that gamification created a more engaging, collaborative, and student-centered learning environment that increased students’ participation and motivation throughout the training process. Furthermore, reflective sessions helped students connect leadership values learned during the games with real-life situations and social interactions. The program also demonstrated strong sustainability and scalability potential for implementation in other educational institutions as an innovative approach to character education and leadership development among secondary school students